Spectrum of Dermatology Referrals from the Pediatric Cancer Unit: A Prospective Observational Study - Akash Agarwal; Saroj Prasad Panda; Maitreyee Panda; Ajaya Kumar Jena (Indian Journal of Paediatric Dermatology, 2025)
Background: Dermatological manifestation in pediatric cancers can occur as part of primary malignancy or cutaneous metastasis, or chemotherapy-associated side-effects. Aim: The aim of this study was to evaluate the cutaneous manifestations in pediatric malignancies and their impact on management. Materials and Methods: A prospective observational study was conducted at a tertiary center between September 2019 and March 2022. All pediatric patients with confirmed malignancy having a cutaneous manifestation were screened for eligibility and their data were recorded. The data were analyzed using SPSS software. Results: Data from 117 patients with a mean age of 7.53 ± 4.41 years were recorded. Twenty-four patients (20.5%) had cutaneous manifestations of an initial malignancy presentation. Nineteen out of 88 patients with acute leukemia (21.5%) had purpuric lesions as the initial presentation. A total of 257 chemotherapy-related skin manifestations were noted in 117 patients with infections being the most common (n = 85, 72.64%), followed by hair changes (n = 59; 50.42%), nail changes (n = 39; 33.33%), and mucosal changes (n = 36; 30.76%). Oral mucositis was the most common mucosal side effect noted in 22 patients, with the majority having underlying hematological malignancy (20/22) and methotrexate-based regimen being the most common culprit (17/22). 44 and 57 out of the total 257 cutaneous manifestations warranted hospitalization and further chemotherapy modification, respectively, with oral mucositis Grade 3 or 4 (n = 12) and varicella (n = 10) being the most common culprits. Conclusion: Our study represents one of the largest study evaluating the cutaneous manifestations of pediatric malignancies including both and chemotherapy-associated. In addition to understanding the various cutaneous manifestations, it is paramount to manage these presentations promptly to reduce disease-related morbidity.